Long-Term Exposure to Inflammation Induces Differential Cytokine Patterns and Apoptosis in Dendritic Cells - Carstensen, Laura Stentoft; Lie-Andersen, Olivia; Obers, Andreas; Crowther, Michael Douglas; Svane, Inge Marie; Hansen, Morten (Frontiers in Immunology, 2019)
The activation of dendritic cells (DCs) has profound implications and governs the control of adaptive immunity. However, long-term activation might drive exhaustion of immune cells and negatively affect functionality. Here, long-term versus short-term exposure to bacterial lipopolysaccharide and interferon (IFN)γ was evaluated on human monocyte-derived DCs. Long-term activated DC1s began to undergo apoptosis concomitant with a profound TAM-receptor and efferocytosis-dependent induction of interleukin (IL)-10. Whereas levels of IL-12p70 and IL-10 were positively correlated upon short-term activation, an inverse association occured upon long-term activation and, while short-term activated CD1a+ DCs were main producers of IL-12p70, CD1a- DCs were the main fraction that underwent apoptosis and released IL-10 upon long-term activation. Moreover, pre-apoptotic long-term activated DCs were no longer able to activate alloreactive IFNγ-responsive T cells present in peripheral blood mononuclear cells from healthy volunteers. The IFNγ response was mediated by IL-12p70, as a strong reduction in IFNγ was observed following blockade with an IL-12p70 neutralizing antibody. Finally, multiplex analysis of DC supernatants revealed a particular pattern of proteins associated with apoptosis, cancer and chronic inflammation partly overlapping with gold standard DCs well-known for their inability to secrete IL-12p70. In conclusion, long-term activated DC1s significantly changed their profile towards a non-functional, tumour-promoting and anti-inflammatory phenotype.